First record of the scuttle fly genus Peromitra (Diptera: Phoridae) from South Korea, with a key to world species - Lee, Jun-Ho; Kim, Sam-Kyu (Zootaxa, 2025)
The genus Peromitra Enderlein is newly recorded from South Korea with six species. Two of them, P. dextra sp. nov. and P. galgori sp. nov., are described as new to science and the other four species, viz. P. agilis (Meigen), P. fimbriata Nakayama & Shima, P. multisetalis (Colyer) and P. ussurica Michailovskaya are new to South Korea. Detailed descriptions with photographs of the six Korean Peromitra species are provided. In addition, taxonomic notes on some Peromitra species based on examination of the type specimens and a revised key to males of world species are given.